Improved fatigue strength of cold forging tools by surface and coating technologies - Hinsel, Christian; Celeghini, Martino; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasti¬city 1990, Proc. of the 6th Int. Conf. on Technology of Plasticity, Vol. 1, 1999)
None
LFT Import::2019-08-05 (1996)